Epinecidin-1, a highly potent marine antimicrobial peptide with anticancer and immunomodulatory activities - Alireza Neshani; Hosna Zare; Mohammad Reza Akbari Eidgahi; Azad Khaledi; Kiarash Ghazvini (BMC, 2019)
Abstract Background Antibiotic-resistant pathogens are an emerging threat in this century. Epinecidin-1 is a multi-functional Antimicrobial Peptide (AMP) produced by Orange-spotted grouper (Epinephelus coioides) has been shown to have extensive potentials as an alternative for current antibiotics. Due to the huge costs for the study and the production of a new drug, if an antimicrobial peptide has other beneficial functions in addition to antimicrobial activities, it would be preferred. Methods In this study, properties and applications of Epinecidin-1 were investigated and addressed comprehensively. To achieve this, the Google Scholar search engine and three databases of PubMed, Scopus, and Web of Science were used. Results Epinecidin-1 is a cationic AMP with an alpha-helical structure. Seven functional usages of this peptide have been reported in the literature including antibacterial, antifungal, antiviral, antiprotozoal, anticancer, immunomodulatory, and wound healing properties. Moreover, this peptide has high potential to be used as an active ingredient in cleaning solutions as well as application in vaccine production. Conclusion Due to significant antimicrobial activities tested on bacteria such as Staphylococcus aureus and Helicobacter pylori and also wound healing properties, Epi-1 has high potential to be considered as an important candidate for the production of new drugs and treatment of various infections including diabetic foot ulcer and peptic ulcer. Moreover, adjuvant-like properties of Epi-1 make it a suitable candidate for the studies related to an adjuvant. Other attractive properties such as anticancer effects have also been reported for this peptide which encourages further studies on this peptide.